การจัดการแบบดั้งเดิมของราษฎร ต่อต้นไม้ที่เหลืออยู่ในพื้นที่นา ท้องที่อำเภอภูเวียง จังหวัดขอนแก่น - ประไชโย, บัวเรศ (วารสารวนศาสตร์ไทย, 2022)
The study was carried out at several villages in Phuwiang District, Khon Kaen Province. 203 Households, from 16 villages located in the outskirt of the Phuwiang Sanitational District, were selected by sampling method. The heads of each household were interviewed by the researcher with the cooperation of some staffs from Khon Kaen Regional Forest Division. The information obtained from the interviewing covered the field of Socioeconomics, Landuse pattern, Wood utilization, and the methods for management of trees remaining in the paddy fields. The age, number of family's member, paddy area and yield, number an species of tree both planted and natural existing were also recorded. The analysis to find out the tree density, ecological system, index of diversity was carried on respectively. The results of the study was shown the indigenous knowledge which the farmers transferred from generation to generation